Relation between Eating Habits and a High Body Mass Index among Freshman Students: A Cross-Sectional Study - GÜNEŞ, FATMA ESRA; BEKİROĞLU, GÜLNAZ NURAL (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2012)
Objectives: This study aimed to examine the relation between eating habits and a high body mass index (BMI) in first-year freshman university students and included 2525 freshman university students 18 to 22 years old from a Turkish population. Methods: in this study, 48% of the students were men. They were asked to complete a questionnaire on their dietary habits including the frequency of their consumption of individual food items, demographic data, and smoking habit. Results: The effects of eating habits on increased BMI (>= 25) were analyzed. Of 2259 subjects included in the analyses, 322 were overweight or obese and 1937 had normal and thin BMI (<25). Multivariate analyses identified male gender, recent weight change, and high number of meals as independent predictors of obesity/overweight. Frequent consumptions of beer, alcoholic drinks other than beer and wine (e.g., spirits including whisky, gin, raid, vodka), coffee, tea, coke, red meat, variety meat, and eggs were associated with a significantly higher risk of obesity/overweight, whereas frequent consumption of snacks was associated with a low risk. Conclusions: Findings of further studies, possibly taking into consideration the absolute quantities of consumption along with cultural and local issues, would guide the adoption of healthier feeding behaviors in this particular age group.
Keywords: eating habits; body mass index; freshman students; obesity; overweight; FAST-FOOD CONSUMPTION; UNIVERSITY-STUDENTS; COLLEGE-STUDENTS; ENERGY-INTAKE; LIFE-STYLE; SNACKING PATTERNS; MEDICAL-STUDENTS; DIETARY HABITS; WEIGHT STATUS; OBESITY RISK